KOMPARASI PEMIKIRAN BERWICK SAYERS DAN MARY MORTIMER TENTANG SISTEM KLASIFIKASI PERPUSTAKAAN - Nurul Fadilla (Jurnal Pustaka Ilmiah, 2020)
This paper focuses on a good library classification system based on the thoughts of Berwick Sayers and Mary Mortimer. It compares and looks at the relevance of these thoughts. This study applied a qualitative approach and comparative descriptive analysis. Both Berwick Sayers and Mary Mortimer have been famous for their works including the library classification system. Based on the results of a comparison between their thoughts, the study found four fundamental differences. The differences cover 1) A good form of classification is easy to use as explicitly proposed by Mary Mortimer because a ‘good version’ for the librarian is not necessarily a ‘good version’ for the library user. Thus, the result will be different. However, if it is easy to use for the user, then it is certainly a good classification form. Meanwhile, Berwick Sayers does not provide an assertive statement but only explains about a good classification; 2) Simple notation versus specific notation; 3) Fitted with a geographical table; 4) Alphabetical versus systematical. Further, the study found four similarities between those thoughts, such as 1) Cover all fields of science; 2) Accommodate new scientific subjects and notations; 3) Develop new science, and 4) Have a supervisory board. Explicitly, the idea that can be implemented in the current library is Mary Mortimer’s thought, Dewey Decimal Classification.